Taṭbīq Al-Manhaj Al-Takamuly Fī Mu’assasāt Al-Ta’līm Al-‘Āly - Mubaraq, Zulfi; Haris, Abd; Suleiman, Musa Izzat Khalil; Bahruddin, Uril (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This study aims to (1) describe the idea of an integrated curriculum in higher education, (2) depict its implementation at the university level, and (3) find out the impact of the curriculum on university development. This research used a qualitative approach. It employed a literature study. The researchers gathered the data from book reviews and related journals. Data analysis involved collecting the data, sorting, presenting, and drawing conclusions. The findings showed that (1) the idea of an integrated curriculum was depicted in a tree-shaped scientific structure; (2) the integrated curriculum was done by requiring all students to learn Arabic and English, as well as providing opportunities for all students to memorize the Quran and practice Islamic life; (3) integrated curriculum contributed to accelerating the development and internationalization of institutions. Moreover, it improved human resources competencies.